2018
DOI: 10.1002/gps.4957
|View full text |Cite
|
Sign up to set email alerts
|

Older men with bipolar disorder: Clinical associations with early and late onset illness

Abstract: Our results indicate that the clinical associations and outcomes of older adults living with BD are not markedly influenced by age of onset. However, mortality data suggest that differences between older adults with BD onset before and after age 60 years should continue to be explored.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 26 publications
0
15
0
1
Order By: Relevance
“…The results showed that regardless of the age of BD onset, these individuals had an increased risk for dementia (Age < 50 ‐ HR 3.46, 95% CI 2.41–4.95; Age ≥ 50–HR 2.26, 95% CI 1.76–2.90). Incident dementia was higher when onset of BD illness was before 50 years and after 60 years, even though this effect was not significant .…”
Section: Resultsmentioning
confidence: 81%
See 2 more Smart Citations
“…The results showed that regardless of the age of BD onset, these individuals had an increased risk for dementia (Age < 50 ‐ HR 3.46, 95% CI 2.41–4.95; Age ≥ 50–HR 2.26, 95% CI 1.76–2.90). Incident dementia was higher when onset of BD illness was before 50 years and after 60 years, even though this effect was not significant .…”
Section: Resultsmentioning
confidence: 81%
“…The systematic review included five cohort studies assessing whether BD is a risk factor for dementia. All studies showed that BD presents with an increased risk for developing dementia . Kessing et al included all inpatients with a main diagnosis of BD, major depression, osteoarthritis, or diabetes from January 1, 1977, to December 31, 1993, with no history of dementia before selection.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Taken together, these results suggest that the course of affective symptoms seems to be relatively benign for most men with BD who reach old age. We are also mindful of the fact that differential mortality could conceivably confound the association between BD with hospital contacts, although that seems an unlikely explanation for our findings because older men with EOBD and LOBD have similar mortality rates during follow up (Almeida et al, 2018a).…”
Section: Discussionmentioning
confidence: 90%
“…Such a bias would have diluted the differences between EOBD and LOBD. In a previous study we have shown that changing the age that defines LOBD has limited effect on clinical associations, which suggests that error associated with the definition of EOBD and LOBD was most likely minimal (Almeida et al, 2018a;Almeida et al, 2016b). We are also mindful of the fact that WADLS records are only available from 1966, which means that earlier mental health contacts would have not been available.…”
Section: Strengths and Limitationsmentioning
confidence: 97%